2016 update of the EULAR recommendations for the management of early arthritis. Issue 6 (15th December 2016) - Combe, Bernard; Landewe, Robert; Daien, Claire I; Hua, Charlotte; Aletaha, Daniel; Álvaro-Gracia, Jose María; Bakkers, Margôt; Brodin, Nina; Burmester, Gerd R; Codreanu, Catalin; Conway, Richard; Dougados, Maxime; et al.
Abstract : Objectives: Since the 2007 recommendations for the management of early arthritis have been presented, considerable research has been published in the field of early arthritis, mandating an update of the 2007 European League Against Rheumatism (EULAR) recommendations for management of early arthritis. Methods: In accordance with the 2014 EULAR Standardised Operating Procedures, the expert committee pursued an approach that was based on evidence in the literature and on expert opinion. The committee involved 20 rheumatologists, 2 patients and 1 healthcare professional representing 12 European countries. The group defined the focus of the expert committee and target population, formulated a definition of 'management' and selected the research questions. A systematic literature research (SLR) was performed by two fellows with the help of a skilled librarian. A set of draft recommendations was proposed on the basis of the research questions and the results of the SLR. For each recommendation, the categories of evidence were identified, the strength of recommendations was derived and the level of agreement was determined through a voting process. Results: The updated recommendations comprise 3 overarching principles and 12 recommendations for managing early arthritis. The selected statements involve the recognition of arthritis, referral, diagnosis, prognostication, treatment (information, education, pharmacological and non-pharmacological interventions), monitoring and strategy. Eighteen items were identified as relevant for future research. Conclusions: These recommendations provide rheumatologists, general practitioners, healthcare professionals, patients and other stakeholders with an updated EULAR consensus on the entire management of early arthritis.